Navigating the Complexities of Molar Incisor Hypomineralization: Challenges and Strategies in Pediatric Dentistry - Zuhair Al-Nerabieah; Muaaz AlKhouli; Mayssoon Dashash (International Journal of Dentistry)
Conclusion: Effective MIH management requires standardized diagnostic protocols, resource advocacy, interdisciplinary collaboration, and holistic patient care. Advancements in research, education, and policy are essential to improve outcomes in pediatric patients. By addressing both clinical and psychosocial challenges, the overall well-being of MIH-affected children can be enhanced.